HUBUNGAN PENGETAHUAN GIZI IBU DAN POLA MAKANBALITADENGAN STATUS GIZI BALITA(12-59 BULAN) DI WILAYAH KERJA PUSKESMAS GANDUS KECAMATAN GANDUS - PALEMBANG TAHUN 2010 - Khotimah, Nyimas Nur; Siregar, Rohanta; Mardiana, Mardiana (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2012)
Nutrition and food give contribution to qualify human resource building in order to perform maximal national building. Nutrition problem in Indonesia and other developing countries still donated in four nutrition problems, they are : Energy Protein Malnutrition (EPM), iron deficiency, yodium deficiency, vitamin A deficiency and obesity in urban. There are thirty mothers of underfive children who have good nutrition knowledge(37,5%) and fifty mothers of underfive children have lack nutrition knowledge (62,5%) in primery health service Gandus district – Palembang city, whereas fourty eight underfive children have good dietary pattern(60%) and thirty two underfive children have lack dietary pattern (40%). From the statistic analysis by using ChiSquare test we get the value p=0.05(p<0.05).The conclution is significant relation in nutrition status of dietary pattern inthat area using indicator body weight/age. We sugest that mothers underfive children need more nutrition knowledge especially good dietary pattern intervation.Through nutrition compaign, discussion etc from health providers in order to increase nutrition status and they can apply good dietary pattern for underfive children so that we do not find underfive children malnourish.